The Ocular Microbiome: Molecular Characterisation of a Unique and Low Microbial Environment - Ozkan, Jerome; Willcox, Mark D. (Current eye research, 2019)
Aim: The ocular surface is continually exposed to bacteria from the environment and traditional culture-based microbiological studies have isolated a low diversity of microorganisms from this region. The use of culture-independent methods to define the ocular microbiome, primarily involving 16S ribosomal RNA gene sequencing studies, have shown that the microbial communities present on the ocular surface have a greater diversity than previously reported. Method: A review of the literature on ocular microbiome research in health and disease. Results: Molecular techniques have been used to investigate the effect of contact lens wear and disease on the microbiota of the ocular surface and eyelids and the immunoregulatory role of the ocular surface microbiota. Studies have shown that compositional changes in the microbiota occur in ocular surface disorders such as blepharitis, trachoma and dry eye and also suggest a role of the ocular and non-ocular microbiome in retinal disease including age-related macular degeneration, glaucoma, uveitis and diabetic retinopathy. However, ocular microbiome studies need to recognise the potential for contamination to impact findings and carefully control each stage of the experimental procedure and to utilise statistical methods to identify contamination signals. Conclusion: The healthy ocular surface is characterised by a relatively stable, comparatively low diversity microbiome with recent findings that the bacteria of the ocular surface appear to have a role in maintaining homeostasis by modulating immune function.